Astrocytic mitochondrial membrane hyperpolarization following extended oxygen and glucose deprivation. - Andrej Korenić; Johannes Boltze; Alexander Deten; Myriam Peters; Pavle Andjus; Lidija Radenović (PLoS ONE)
Astrocytes can tolerate longer periods of oxygen and glucose deprivation (OGD) as compared to neurons. The reasons for this reduced vulnerability are not well understood. Particularly, changes in mitochondrial membrane potential (Δψ(m)) in astrocytes, an indicator of the cellular redox state, have not been investigated during reperfusion after extended OGD exposure. Here, we subjected primary mouse astrocytes to glucose deprivation (GD), OGD and combinations of both conditions varying in duration and sequence. Changes in Δψ(m), visualized by change in the fluorescence of JC-1, were investigated within one hour after reconstitution of oxygen and glucose supply, intended to model in vivo reperfusion. In all experiments, astrocytes showed resilience to extended periods of OGD, which had little effect on Δψ(m) during reperfusion, whereas GD caused a robust Δψ(m) negativation. In case no Δψ(m) negativation was observed after OGD, subsequent chemical oxygen deprivation (OD) induced by sodium azide caused depolarization, which, however, was significantly delayed as compared to normoxic group. When GD preceded OD for 12 h, Δψ(m) hyperpolarization was induced by both GD and subsequent OD, but significant interaction between these conditions was not detected. However, when GD was extended to 48 h preceding OGD, hyperpolarization enhanced during reperfusion. This implicates synergistic effects of both conditions in that sequence. These findings provide novel information regarding the role of the two main substrates of electron transport chain (glucose and oxygen) and their hyperpolarizing effect on Δψ(m) during substrate deprivation, thus shedding new light on mechanisms of astrocyte resilience to prolonged ischemic injury.